Anorexia, pain and peripheral neuropathy are associated with a decrease in quality of life in patients with advanced pancreatic cancer receiving outpatient chemotherapy - a retrospective observational study - Hironori Fujii; Maaya Koda; Shiori Sadaka; Koichi Ohata; Hiroko Kato-Hayashi; Hirotoshi Iihara; Ryo Kobayashi; Takuma Ishihara; Shinya Uemura; Takuji Iwashita; Hideki Hayashi; Tadashi Sugiyama; et al. (BMC, 2021)
Abstract Background Cancer chemotherapy usually improves clinical outcomes in patients with advanced pancreatic cancer (APC), but can also cause moderate-to-severe adverse events (AEs). We investigated the relationship between moderate-to-severe AEs and quality of life (QOL) in patients with APC who received outpatient chemotherapy. Methods We recruited APC patients who received outpatient chemotherapy in Gifu University Hospital between September 2017 and December 2018. Adverse events related to chemotherapy were assessed by a pharmacist collaborating with a physician using common terminology criteria for AEs (CTCAE) ver 4.0, and QOL of patients was self-assessed by patients using the five-level EuroQol five-dimensional questionnaire (EQ-5D-5L Japanese edition 2). Associations between the EQ-5D-5L utility value and serious AEs were assessed using proportional odds logistic regression. Results A total of 59 patients who received 475 chemotherapy cycles were included. The proportional odds logistic regression indicated that grade ≥ 2 anorexia, pain and peripheral neuropathy were significantly correlated with a decreased EQ-5D-5L utility value. Pharmaceutical intervention for these AEs significantly improved the patients' EQ-5D-5L utility value. Conclusions Anorexia, pain and peripheral neuropathy were significantly associated with a decrease in QOL. It is assumed that appropriate pharmaceutical intervention with particular emphasis on these AEs can improve the QOL of pancreatic cancer patients receiving outpatient chemotherapy.